Selectively promiscuous opioid ligands: discovery of high affinity/low efficacy opioid ligands with substantial nociceptin opioid peptide receptor affinity - Kumar, Vinod; Ridzwan, Irna Elina; Grivas, Konstantinos; Lewis, John W; Clark, Mary J; Meurice, Claire; Jimenez-Gomez, Corina; Pogozheva, Irina; Mosberg, Henry; Traynor, John R; Husbands, Stephen M (American Chemical Society, 2014)
Emerging clinical and preclinical evidence suggests that a compound displaying high affinity for μ, κ, and δ opioid (MOP, KOP, and DOP) receptors and antagonist activity at each, coupled with moderate affinity and efficacy at nociceptin opioid peptide (NOP) receptors will have utility as a relapse prevention agent for multiple types of drug abuse. Members of the orvinol family of opioid ligands have the desired affinity profile but have typically displayed substantial efficacy at MOP and or KOP receptors. In this study it is shown that a phenyl ring analogue (1d) of buprenorphine displays the desired profile in vitro with high, nonselective affinity for the MOP, KOP, and DOP receptors coupled with moderate affinity for NOP receptors. In vivo, 1d lacked any opioid agonist activity and was an antagonist of both the MOP receptor agonist morphine and the KOP receptor agonist ethylketocyclazocine, confirming the desired opioid receptor profile in vivo.